Level of Cardiovascular Disease Risk and Associated Factors among Clients on Highly Active Antiretroviral Therapy in Vihiga County, Kenya - Lilian Amugitsi; Grace Mbuthia; Damaris Ochanda (Evidence-Based Nursing Research)
Context: HIV/AIDS is still a public health concern globally, especially in sub-Saharan Africa and Kenya. HIV-positive clients are initiated on highly active antiretroviral therapy (HAART) to reduce the multiplication of HIV and improve their immunity. These clients are at an increased cardiovascular disease risk due to a complex interplay of factors, including traditional cardiovascular risk factors such as smoking cigarettes, obesity due to inactivity, and diabetes.